Information, Institutions, and Governance - Wantchekon, Leonard (2019)
Leonard Wantchekon POLICY SEMINAR Information, Governance, and Rural Service Delivery Co-Organized by IFPRI and the CGIAR Research Program on Policies, Institutions, and Markets (PIM)